Estimating the emergency care workforce in South Africa - Ritika Tiwari; Raveen Naidoo; René English; Usuf Chikte (AOSIS, 2021)
Background: Emergency care is viewed as a fundamental human right in South Africa's constitution. In the public sector, all emergency medical services (EMS) come under the Directorate: Emergency Medical Services and Disaster Medicine at the National Department of Health (NDoH), which provides regulation, policy and oversight guidance to provincial structures. Aim: The aim of the study is to understand the supply and status of human resources for EMS in South Africa. Setting: This research was undertaken for South Africa using the Health Professions Council of South Africa (HPCSA) database from 2002 to 2019. Methods: A retrospective record-based review of the HPCSA database was undertaken to estimate the current registered and future need for emergency care personnel forecasted up to 2030. Results: There are 76% Basic Ambulance Assistants registered with HPCSA. An additional 96 000 personnel will be required in 2030 to maintain the current ratio of 95.9 registered emergency care personnel per 100 000 population. The profile of an emergency care personnel employed in South Africa is likely to be a black male in the age group of 30-39-years, residing in one of the economically better-resourced provinces. Conclusion: It is time that the current educational framework is revised. Policy interventions must be undertaken to avoid future shortages of the trained emergency care personnel within South Africa.